Responses of bovine chimaeras combining trypanosomiasis resistant and susceptible genotypes to experimental infection with Trypanosoma congolense - Naessens, Jan; Leak, S.G.A.; Kennedy, D.J.; Kemp, Stephen J.; Teale, A.J. (2001)
West African N'Dama cattle have developed a genetic capacity to survive, reproduce and remain productive under trypanosomosis risk. The cellular and molecular bases of this so-called trypanotolerance are not known, but the trait is manifested by the N'Dama's greater capacity to control parasitaemia and anaemia development during an infection. In order to examine the role of the haematopoietic system in trypanosomosis, the tendency for the placentas of bovine twin embryos to fuse have been exploited. Placental fusion in cattle results in bone marrow chimaerism in twins. By comparison with the N'Dama, cattle of the East African Boran breed are relatively susceptible. The role of the haemopoietic system in trypanotolerance by comparing the performance of five chimaeric Boran/ N'Dama twin calves with that of single-tons of the two breeds was evaluated.